Eurycercus (Eurycercus) Baird 1843 - Bekker, Eugeniya I.; Kotov, Alexey A.; Taylor, Derek J. (Zenodo, 2012)
Key for determination of adult parthenogenetic females of the Holarctic species of Eurycercus ( Eurycercus ) emend. nov. 1 Dorsal head pores lack a bubble-like projection and are located on a prominent transverse fold (indentation); a median keel passes through whole carapace dorsum.................................................................... 2 - Dorsal head pores possess a bubble-like projection and are located on a prominent transverse fold (indentation) or on a flat head shield; a median keel is completely absent or expressed only in the posterior portion of the carapace dorsum......... 3 2 Small (seldom as large as 2 mm), body very strongly compressed laterally, dorsal margin of head flattened or even slightly concave between compound eye and median head pore, the smallest seta IDL very short............ E. microdontus Frey, 1978 - Large species, body moderately compressed laterally, dorsal margin of head regularly convex, the smallest seta of IDL of moderate size................................................................. E. lamellatus (O. F. Müller, 1776) 3 Bubble-like projection on prominent transverse fold, median keel present in posterior portion of carapace dorsum.................................................................................................... E. beringi sp. nov . - Bubble-like projection on flat head shield, median keel absent................................................. 4 4 Median labral keel short, reaching approximately middle of antenna I...................... E. pompholygodes Frey, 1975 - Median labral keel large, approximately reaching tip of antenna I................................................. 5 5 Apex of median labral keel distinctly angled.................................... E. nipponica Tanaka & Fujita, 2002 - Apex of median labral keel rounded.......................................................................... 6 6 Hook-like seta on IDL especially strong, its base occupies the whole top of IDL............... E. macracanthus Frey, 1973 - Hook-like seta on IDL not so strong, its base occupies only a part of top of IDL................ E. longirostris Hann, 1982 : Published as part of Bekker, Eugeniya I., Kotov, Alexey A. & Taylor, Derek J., 2012, A revision of the subgenus Eurycercus (Eurycercus) Baird, 1843 emend. nov. (Cladocera: Eurycercidae) in the Holarctic with the description of a new species from Alaska, pp. 1-40 in Zootaxa 3206 (1) on pages 32-33, DOI: 10.11646/zootaxa.3206.1.1, http://zenodo.org/record/5248211 : {"references": ["Frey, D. G. (1978) A new species of Eurycercus (Cladocera, Chydoridae) from the Southern United States. Tulane Studies in Zoology and Botany, 20, 1 - 25.", "Muller, O. F. (1776) Zoologiae Danicae prodromus, seu animalium Daniae et Norvegiae indigenarum characteres, nomina, et synonyma imprimis popularium. (Zoologiae Danicae Prodromus). Typis Hallageriis, N. Mulleri aviae regiae typographie et filii, Havniae (Copenhagen), pp. i - xxxii + 1 - 282.", "Frey, D. G. (1975) Subgeneric differentiation within Eurycercus (Cladocera, Chydoridae) and a new species from Northern Sweden. Hydrobiologia, 46, 263 - 300.", "Tanaka, M. & Fujita, S. (2002) Study on the plankton from Lake Utonai-numa, Hokkaido. Yokkaichi University Journal of Environmental and Information Sciences, 6, 1 - 25 (in Japanese).", "Hann, B. J. (1982) Two new species of Eurycercus (Bullatifrons) from Eastern North America (Chydoridae, Cladocera). Taxonomy, ontogeny, and biology. Internationale Revue der gesamten Hydrobiologie und Hydrographie, 67, 585 - 610."]}